Penerapan Terapi Murotal Al-Qur’an Untuk Menurunkan Kecemasan Kecemasan Pada Pasien Pre Operasi - Adhin Al Kasanah; Mega Arianti Putri; Yudha Fika Diliana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
In the pre-operative phase, clients experience various discomforts that arise due to ignorance about the procedure, fear of surgery and uncertainty of the results of the operation. One of the problems that often arises is anxiety. . Efforts to reduce anxiety levels in pre-operative patients are by providing Al-Qur'an murottal therapy. Al-Qur'an murottal therapy is one of the therapies that can provide a calming effect on the soul and eliminate anxiety. The results of community service showed that before being given murottal therapy, 72.2% of participants experienced moderate anxiety and after being given intervention, 83.3% of participants experienced a decrease in anxiety to the mild anxiety category. The time that can be applied in providing Al-Qur'an murottal therapy is at least 15 minutes to provide a relaxing effect and reduce anxiety in pre-operative patients.